Economic theory and the underdeveloped countries - Myint, Hla. (New York : Oxford University Press, 1971)
The volume contains most of the author's papers on the economics of the underdeveloped countries written since the early days of the subject in the 1950s. The papers in this volume are concerned with the middle level of analysis between "pure" formal economic theory and detailed empirical studies of particular underdeveloped countries. Their aim is to examine the realism and the relevance of theoretical concepts and doctrines, both orthodox and modern, in relation to the broadly observable patterns of economic change, the salient features of the economic situation, and the general aims of development policy in the underdeveloped countries.
Includes bibliographical footnotes and index.
rpm 30/08/2017
Loans
Keywords: Economic development; Developing countries